Relationship between Knowledge and adherence to Use of TB Drugs in adults in Idaman Banjarbaru Hospital: Hubungan Pengetahuan terhadap Kepatuhan Minum Obat TBC Dewasa di RSD Idaman Banjarbaru - Wati, Helmina; Kurniawan, Guntur; Abdurrahman, Faizah (Universitas Tadulako, 2024)
Background: Tuberculosis (TB) is the disease that causes the highest mortality worldwide. One of the causes is the bacteria Mycobacterium tuberculosis. Knowledge and adherence are very important in TB treatment to achieve therapeutic success. Objectives: This study aims to see the relationship between the level of knowledge and adherence to taking medication for adult TB patients at Idaman Banjarbaru Hospital. Methods: This type of research is descriptive research with a cross-sectional research design, prospectively taken in March–June 2023. The total sampling technique was employed to select 42 patients. The data were collected via a validated online questionnaire and subsequently analysed using the Fisher Exact SPSS test with a 95% confidence level. Results: The results showed that patients had a good level of knowledge of as many as 32 people (76.2%) and had less knowledge of as many as 10 people (23.8%). The value of patient compliance in taking medication was 29 people (69%), and disobedient as many as 13 people (31%). Conclusion: The statistical analysis results indicated a statistically significant relationship between knowledge and compliance with medication in TB patients at Idaman Banjarbaru Hospital (p < 0.05). This implies that an individual's willingness to comply with medication regimens is significantly influenced by their knowledge about the prescribed treatment.